2023
DOI: 10.3389/fvets.2023.1249951
|View full text |Cite
|
Sign up to set email alerts
|

External mechanical perturbations challenge postural stability in dogs

Christiane Lutonsky,
Christian Peham,
Marion Mucha
et al.

Abstract: This study aimed to explore the effect of external mechanical perturbations on postural stability (PS) in dogs using the body center of pressure (COP). Thirteen sound adult dogs were included in this study. PS was tested during quiet standing on a pressure measurement plate. The conditions included a standard standing measurement and external mechanical perturbations conducted using six settings on a motorized training platform with different intensities of speed and amplitude. Measurement conditions were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Carrillo et al [ 17 ] demonstrated a higher sway in lame dogs with CCL rupture and elbow dysplasia compared to healthy ones; hence, muscle strength could be of importance for balance control in dogs with stifle injury. Recent studies [ 18 , 19 , 20 , 21 ] measured postural sway by observing changes in the center of pressure (COP), using force or pressure plates, in both the mediolateral and craniocaudal directions. Lutonsky et al [ 19 ] used three-dimensional circular movements to challenge standing balance in healthy dogs and found a significant increase in multiple COP parameters with greater movement in the mediolateral direction than craniocaudal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrillo et al [ 17 ] demonstrated a higher sway in lame dogs with CCL rupture and elbow dysplasia compared to healthy ones; hence, muscle strength could be of importance for balance control in dogs with stifle injury. Recent studies [ 18 , 19 , 20 , 21 ] measured postural sway by observing changes in the center of pressure (COP), using force or pressure plates, in both the mediolateral and craniocaudal directions. Lutonsky et al [ 19 ] used three-dimensional circular movements to challenge standing balance in healthy dogs and found a significant increase in multiple COP parameters with greater movement in the mediolateral direction than craniocaudal.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [ 18 , 19 , 20 , 21 ] measured postural sway by observing changes in the center of pressure (COP), using force or pressure plates, in both the mediolateral and craniocaudal directions. Lutonsky et al [ 19 ] used three-dimensional circular movements to challenge standing balance in healthy dogs and found a significant increase in multiple COP parameters with greater movement in the mediolateral direction than craniocaudal. Dogs with arthrosis of the stifle joint have shown an increase in mediolateral movements compared to healthy dogs [ 21 ], while dogs with osteoarthritis of the elbow or hip joint indicated compensatory changes in the COP within the paws [ 20 ].…”
Section: Introductionmentioning
confidence: 99%